Cydonia oblonga-Seed-Mucilage-Based pH-Sensitive Graft Copolymer for Controlled Drug Delivery-In Vitro and In Vivo Evaluation - Muhammad Sarfraz; Ume Ruqia Tulain; Alia Erum; Nadia Shamshad Malik; Arshad Mahmood; Sumaira; Sidra Aslam; Mansur Abdullah Sandhu; Muhammad Tayyab (MDPI AG, 2023)
The primary objective of this study was to assess the potential utility of quince seed mucilage as an excipient within a graft copolymer for the development of an oral-controlled drug delivery system. The Cydonia oblonga-mucilage-based graft copolymer was synthesized via a free radical polymerization method, employing potassium per sulfate (KPS) as the initiator and N, N-methylene bisacrylamide (MBA) as the crosslinker. Various concentrations of monomers, namely acrylic acid (AA) and methacrylic acid (MAA), were used in the graft copolymerization process. Metoprolol tartarate was then incorporated into this graft copolymer matrix, and the resultant drug delivery system was subjected to comprehensive characterization using techniques such as Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The swelling behavior of the drug delivery system was evaluated under different pH conditions, and in vitro drug release studies were conducted. Furthermore, pharmacokinetic parameters including the area under the curve (AUC), maximum plasma concentration (Cmax), time to reach Cmax (Tmax), and half-life (t1/2) were determined for metoprolol-loaded hydrogel formulations in rabbit plasma, and these results were compared with those obtained from a commercially available product. The key findings from the study include observations that higher concentrations of acrylic acid (AA) and Cydonia oblonga mucilage (CM) in the graft copolymer enhanced swelling, while the opposite trend was noted at elevated concentrations of methacrylic acid (MAA) and N, N-methylene bisacrylamide (MBA). FTIR analysis confirmed the formation of the graft copolymer and established the compatibility between the drug and the polymer. SEM imaging revealed a porous structure in the prepared formulations. Additionally, the swelling behavior and drug release profiles indicated a pH-sensitive pattern. The pharmacokinetic assessment revealed sustained release patterns of metoprolol from the hydrogel network system. Notably, the drug-loaded formulation exhibited a higher Cmax (156.48 ng/mL) compared to the marketed metoprolol product (96 ng/mL), and the AUC of the hydrogel-loaded metoprolol was 2.3 times greater than that of the marketed formulation. In conclusion, this study underscores the potential of quince seed mucilage as an intelligent material for graft-copolymer-based oral-controlled release drug delivery systems.